Complex-Radical Terpolymerization of Maleic Anhydride (Styrene), Allyl Propionate and Methyl Methacrylate - L. V. Medyakova; Z. M. Rzaev; A. S. Mamedov; M. A. Mamedova (Eurasian Chemico-Technological Journal, 2000)
The radical terpolymerization reactions of the acceptor-donor-acceptor and donor-acceptor-donor systems, maleic anhydride (MA)-allyl propionate (AP)-methyl methacrylate (MMA) and styrene (St)-MMA-AP, had been studied. The terpolymerizations were carried out in methyl ethyl ketone at 60-75 °C in the presence of 2,2’-azoisobutyronitrile (ABIN) used as the initiator. Some kinetic parameters and copolymerization constants - for both, system were determined by dilatometric and Kelen-Tudos or Seiner-Lift methods. The obtained results are discussed in terms of the free monomer and complex chain growth models. It is shown that terpolymerization was carried out at a stage close to binary copolymerization of MA...AP complex with free MMA and St...MMA complex with AP in the both studied system, respectively. These systems are also used as model for interpretation of cyclocopolymerization mechanism in allyl methactylate-MA (or St) system. DTA and TGA analyses indicated the relatively high thermal stability of St-MMA-AP terpolymer. It is shown that this terpolymer decomposes through a one-step reaction at 310 °C, however MA-AP-MMA terpolymer decomposes through a multi-step reactions at 150, 260 and 310 °C.